Women's Transitions in the Labour Market as a Result of Childbearing: The Challenges of Formal Sector Employment in Indonesia - Lisa A. Cameron; Diana Contreras Suarez; Yi-Ping Tseng (Institute of Labor Economics (IZA), 2023)
Although it is well established that women's labour force participation drops markedly with marriage and childbearing, surprisingly little is known about women's labour market transitions, especially in developing countries. This paper uses the Indonesian Family Life Survey to track the employment histories of over 9,000 women across a period of more than 20 years, observing them as they get married and have children. The data show that large numbers of Indonesian women drop out of the labour market as a result of marriage and childbearing. The difficulty of maintaining formal sector employment emerges as a key problem. Having worked in the formal sector prior to the birth of a first child reduces the probability of working in the year following the birth by 20 percentage points and reduces the probability of returning to the labour market thereafter by 3.6 percentage points. Further, to the extent that women do return to work, formal sector employment is associated with greater delays in returning - women are more likely to return to work in the formal sector only once their child starts primary school, while in the informal sector they return earlier. We find little evidence of women switching from the formal to the informal sector. Formal sector labour market policies such as flexible work hours; compressed work weeks; part-time work (with the same career opportunities and benefits as full-time work); the ability to work from home; and work-based childcare are likely to boost women's labour force participation, with consequent boosts to economic productivity and prosperity.
Keywords: J20; J16; O15; 330; female labour force participation; labour market transitions; economic development; childbearing